2016
DOI: 10.18051/univmed.2016.v35.40-45
|View full text |Cite
|
Sign up to set email alerts
|

Black sugarcane decoction reduces rat brain ischemia

Abstract: BACKGROUNDThere are people in Yogyakarta, who use black sugarcane decoction (BSD) to prevent stroke. BSD contains policosanol and antioxidants. It has been proven that policosanol can reduce global ischemia in Mongolian gerbils. This study aims to evaluate the effect of BSD on brain ischemia in a rat stroke model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The depletion of the bax protein expression on hippocampal part of the rats' brain with black sugarcane administration is also followed by the depletion of the volume of the brain ischemia as well. This result matches previous study, where the lower number of the brain ischemia was also found in the post-tBCCAOrats's brain that received boiled sugarcane water (4) . The observation of the ischemia volume of the rat brain is performed with TTC staining.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The depletion of the bax protein expression on hippocampal part of the rats' brain with black sugarcane administration is also followed by the depletion of the volume of the brain ischemia as well. This result matches previous study, where the lower number of the brain ischemia was also found in the post-tBCCAOrats's brain that received boiled sugarcane water (4) . The observation of the ischemia volume of the rat brain is performed with TTC staining.…”
Section: Discussionsupporting
confidence: 92%
“…The administration of 200 mg/ kgBBpolicosannol on stroke-induced Mongolian gerbils can lower the cerebral ischemic (3) . Previous studies had proven that boiled water from boiled black sugarcane can lower the ischemia volume of the rats' brain post-BCCAO (4) . The mechanism of the lowering of ischemia volume itself is not yet known.…”
Section: Introductionmentioning
confidence: 99%